Characteristics of the Disease Progression and Hospital Treatment of Children with Systemic Juvenile Idiopathic Arthritis: First Results from the Analysis of the All-Russian Register of the Union of Pediatricians of Russia - E. I. Alexeeva; O. L. Lomakina; S. I. Valieva; T. M. Bzarova; I. P. Nikishina; Ye. S. Zholobova; S. R. Rodionovskaya; M. I. Kaleda; L. A. Galstyan; I. B. Alakaeva; Ye. A. Korotkova; A. V. Artyomov; et al. (Вопросы современной педиатрии, 2016)
Objective: Our aim was to study demographic and clinical characteristics of patients with systemic juvenile idiopathic arthritis (sJIA), timing of diagnosis and routing of the children after the onset of the disease according to the All-Russian Register of the Union of Pediatricians of Russia.Methods: Retrospective study (1998–2015) analyzing indicators from 384 children with sJIA.Results: The majority of patients live in the Central and Volga Federal Districts — 157 (40.9%) and 68 (17.7%) patients, respectively. The ratio of girls to boys is 1.25:1; 281 (73.2%) children got sick under the age of 5. In 35 (9.1%) children the disease is hereditary. The trigger factor in 1/3 of patients was an infection. At the onset of the disease, fever was recorded in all patients, rash — in 190 (49.5%), enlargement of the liver and/or spleen — in 150 (39.1%), and serositis — in 56 (14.6%) patients. 17 (4.4%) children had 5 manifestations of systemic disease, 117 (30.5%) — 4, 64 (16.7%) — 3, 73 (19.0%) and 73 (19.0%) — 2 and 1. 175 (45.6%) children had arthritis at the onset of the disease and extra-articular manifestations were observed for 6 months. 7 (1.8%) patients were hospitalized to the specialized rheumatology departments, 50 (13.0%) — to the cardiologic departments, and 190 (49.5%) — to the pediatric departments. 250 (65.1%) patients were diagnosed with an infectious disease. None of the patients was diagnosed with sJIA within first 6 weeks. The average duration of the disease from the onset to diagnosis was 2.0 ± 15.5 (0–139) months, from the onset to the admission to a special department of the federal research center — 8.0 ± 29.3 (0–146) months, from diagnosis to the admission to the federal research center — 3.0 ± 28.0 (0–138) months; 50 (13.1%) patients were hospitalized without a diagnosis (established at the federal research center).Conclusion: According to the All-Russian Register, sJIA is characterized by aggressive beginning at an early age with severe extra-articular manifestations and late addition of the articular syndrome. In most cases, the verification of diagnosis and admission of patients to the specialized rheumatology departments of the federal research center were carried out in later periods.